Eksploitasi terhadap Anak yang Bekerja di Indonesia - Iryani, Beta S.; Priyarsono, D. S. (Jurnal Ekonomi dan Pembangunan Indonesia, 2013)
This study investigated the severity of exploitation of working children and factors determining exploitation of working children. This study used data resulted from National Labor Force Survey (Sakernas) 2011 and utilized logistic regression as the analytical tool. Based on the severity of exploitation, there are three provinces which are always of high value severity of exploitation, namely DKI Jakarta, Banten, and West Java. Education level of household is an influential factor of exploitation measured by working hours and access to education. The lower level of education of head of household, the greater chance the child to be exploited. As for the exploitation measured by wage, girls have a chance 2.357 times greater than that of boys to be for exploited measured by wages.